Penyuluhan tentang Gambaran Diabetes Melitus pada Wanita Usia Subur di Desa Penyengat Olak Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi Tahun 2019 - Dewi Nopiska Lilis; Imelda Imelda (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
The percentage of diabetes mellitus in women of reproductive age needs to be monitored and watched out for. Women with diabetes before pregnancy are more likely to have babies with congenital defects if their glycemic control is below optimal during the first trimester of pregnancy. Target and outcome: to increase knowledge and mindset on the health of women of childbearing age. The goal is to increase health knowledge about the picture of diabetes mellitus in women of childbearing age and changes in behavior from information provided through counseling and giving leaflets as reading material to get used to living healthy and away from things that aggravate health conditions, especially the picture of diabetes mellitus in women of childbearing age. Implementation methods: administrative preparation, socialization, presentation by providing counseling and distribution of leaflets about the description of diabetes mellitus to women of childbearing age in Penyegat Olak Village, Jambi Sub-district, Outer City, Muaro Jambi Regency in 2019, and finally a discussion. Results: Implementation of counseling and distribution of leaflets on the description of diabetes mellitus was given to 40 women of childbearing age. Evaluation carried out after the mother has been given counseling can explain an increase in health knowledge about the picture of diabetes mellitus in women of childbearing age. Behavior changes in women of childbearing age include implementing good things, getting used to living healthy and staying away from things that aggravate the condition of women with diabetes mellitus